Bycie – nie bycie, prawda – fałsz w koncepcji Arystotelesa - Wesoły, Marian Andrzej (Peitho. Examina Antiqua, 2021)
The basis of Aristotle’s arguments about truth and falsity is formulated syntactically according to the distinctions of ‘to be’ as the predicative affirmation - composition and, correspondingly, ‘not to be’ as negation – separation. As the nominal defining characteristic of falsity is contradiction, so of truth is non-contradiction. The expression of truth or falsity in the declarative sentence of affirmation or negation is a function of thinking as a human cognitive disposition under the semantic figures of categorical predication. In addition, we cite Aristotle’s more important texts on the true intellection of non-composites (indivisibles), the investigation of truth and probability, the diagnosis of falsehood, the truthfulness and lying. Finally, a mention of modern adaptations of Aristotle’s concept of truth.